Determination of Trace/Toxic Mineral Risk Levels for Different Aged_x000D_ Consumers of Three Fish Species Caught in the Marmara Sea - (:unkn) unknown (My University, 2019)
The Marmara Sea is a semi closed fishing area in Turkey and has valuable fish species such as thecommon sole, black scorpionfish and horse mackerel. Domestic waste, generated by the population of over 25 million living in the coastal zone as well as industrial facilities in the region are themain causes of pollution in the Marmara Sea. In the current study, the levels of toxic metals (arsenic, cadmium, mercury, and lead) in samples of three fish tissue were analysed over a year-longperiod and compared with international results. The health risks for different age groups causedby the consumption of these fish were estimated. The results revealed that regular weekly consumption of sole and horse mackerel caught from the Marmara Sea posed health risks for childand youth populations. These fish species should be consumed more carefully due to potentialarsenic-related hazards and carcinogenic risks for vulnerable consumer groups.